Modernism and Theology - Rzepa, Joanna. author. (orcid)0000-0002-5485-2204 Link aut Link
XIX, 438 p. 2 illus.
Keywords: 'Joanna Rzepa’s Modernism and Theology forcefully upends the provincial secularization thesis of Anglo-American literary modernism by placing it in the larger international and historical context of theological modernism, showing how major writers from different cultures and languages have explored and asserted the primacy of spiritual and mystical elements of literature over secularism and materialism. This revolutionary study will have a lasting impact on future studies of literary modernism and generate expansive scholarship and revaluation in the field.' —Ronald Schuchard, General Editor, The Complete Prose of T. S. Eliot This is the first book-length study to examine the interface between literary and theological modernisms. It provides a comprehensive account of literary responses to the modernist crisis in Christian theology from a transnational and interdenominational perspective. It offers a cultural history of the period, considering a wide range of literary and historical sources, including novels, drama, poetry, literary criticism, encyclicals, theological and philosophical treatises, periodical publications, and wartime propaganda. By contextualising literary modernism within the cultural, religious, and political landscape, the book reveals fundamental yet largely forgotten connections between literary and theological modernisms. It shows that early-twentieth-century authors, poets, and critics, including Rainer Maria Rilke, T. S. Eliot, and Czesław Miłosz, actively engaged with the debates between modernist and neo-scholastic theologians raging across Europe. These debates contributed to developing new ways of thinking about the relationship between religion and literature, and informed contemporary critical writings on aesthetics and poetics.